Prevention of peptic ulcers with esomeprazole in patients at risk of ulcer development treated with low-dose acetylsalicylic acid: a randomised, controlled trial (OBERON). Issue 10 (17th March 2011) - Scheiman, James M; Devereaux, P J; Herlitz, Johan; Katelaris, Peter H; Lanas, Angel; Veldhuyzen van Zanten, Sander; Nauclér, Emma; Svedberg, Lars-Erik
Abstract : Objective: To determine whether once-daily esomeprazole 40 mg or 20 mg compared with placebo reduces the incidence of peptic ulcers over 26 weeks of treatment in patients taking low-dose acetylsalicylic acid (ASA) and who are at risk for ulcer development. Design: Multinational, randomised, blinded, parallel-group, placebo-controlled trial. Setting: Cardiology, primary care and gastroenterology centres (n=240). Patients: Helicobacter pylori -negative patients taking daily low-dose ASA (75–325 mg), who fulfilled one or more of the following criteria: age ≥18 years with history of uncomplicated peptic ulcer; age ≥60 years with either stable coronary artery disease, upper gastrointestinal symptoms and five or more gastric/duodenal erosions, or low-dose ASA treatment initiated within 1 month of randomisation; or age ≥65 years. All patients were ulcer-free at study entry. Interventions: Once-daily, blinded treatment with esomeprazole 40 mg, 20 mg or placebo for 26 weeks. Main outcome measures: The primary end point was the occurrence of endoscopy-confirmed peptic ulcer over 26 weeks. Results: A total of 2426 patients (52% men; mean age 68 years) were randomised. After 26 weeks, esomeprazole 40 mg and 20 mg significantly reduced the cumulative proportion of patients developing peptic ulcers; 1.5% of esomeprazole 40 mg and 1.1% of esomeprazole 20 mg recipients, compared with 7.4% of placebo recipients, developed peptic ulcers (both p<0.0001 vs placebo). Esomeprazole was generally well tolerated. Conclusions: Acid-suppressive treatment with once-daily esomeprazole 40 mg or 20 mg reduces the occurrence of peptic ulcers in patients at risk for ulcer development who are taking low-dose ASA. Clinical trial registration number: ClinicalTrials.gov identifier: NCT00441727 .